After arrival, the problems facing refugees and their families : a clinical legal response - Marson, James; Ferris, Katy (Northumbria University Library, 2018)
Since 2016, a Refugee Family Reunion Law Clinic has operated from Sheffield Hallam University’s Helena Kennedy Centre for International Justice (hereafter HKC Law Clinic). Given the austerity-driven political agenda of the UK government in cutting public funding to advisory services, the effects of LASPO and a continuing refugee crisis, refugees in many parts of the UK were in need of legal and non-legal assistance. To fill this gap in services university law clinics, including our own, began to offer specialised services to assist the refugee population. This has included family reunion and exceptional case funding applications, and expert legal advice for individuals who find themselves stateless, yet in many instances the formal assistance ends at this stage. The HKC Law Clinic and its staff have remained in contact with many of our refugee clients (some are now engaged as interpreters). Through this interaction we have observed a particular problem of the lack of post-arrival support for refugees and their families. Developing the Therapeutic Jurisprudence philosophy upon which the clinic is based, and thus ensuring a therapeutically positive experience for the Clinic’s users, we have begun a process of creating a more holistic clinical experience. Following the refugee clients’ successful family reunion application, and when building their new lives together in the local region, our clinic offers a range of support services to assist in the pragmatic issues facing the family. This aspect of the HKC Law Clinic is in its infancy, but this paper aims to demonstrate what university law clinics can achieve and provides examples of our experiences so far.